Validation of a microfluidic platform to measure total therapeutic antibodies and incurred sample reanalysis performance. (October 2014) - Magana, Ivan; Macaraeg, Chris R; Zhang, Liana; Ma, Mark; Thway, Theingi M
Background: A microfluidic platform-based assay was validated to measure a humanized or fully human IgG in rat serum samples.Materials & methods: The cumulative assessment for accuracy and precision was performed with three accuracy and precision runs.Results: The inter-assay accuracy (mean %bias) ranged from −4.3 to 3.8%, and inter-batch %CV ranged from 5.0 to 9.2%. The method acceptance criterion was determined as 15% total error. The assay dynamic range was 50 to 10000 ng/ml. Incurred sample reanalysis passed with 95% of samples meeting incurred sample reanalysis acceptance criteria. Potential carryover effect was not observed.Conclusion: This study demonstrated the need for evaluating additional platform-specific processes when new technologies are employed to ensure the reproducibility of a successfully validated microfluidic platform method.